Novel DNA methylation biomarkers in enhancer regions with chromatin interactions for diagnosis of non‐small‐cell lung cancer - Zhixian Zhu; Qiangwei Zhou; Pengpeng Guan; Yuanhui Sun; Guoliang Li (MedComm – Oncology, 2023)
Abstract Lung cancer is the leading cause of cancer‐related deaths worldwide. DNA methylation has been recognized as a potential biomarker for lung cancer diagnosis. Most reported DNA methylation biomarkers focus on promoter regions, leaving enhancer regions largely unexplored. Here, we employed multiomics data to identify DNA methylation biomarkers for non‐small‐cell lung cancer diagnosis. Especially, we linked enhancers to their target genes using long‐range chromatin interactions for biomarker prediction. We discovered two sets of DNA methylation biomarkers: one in promoter regions and another in enhancer regions. Both achieved extremely high sensitivity and specificity in five independent validation data sets. Compared with three other reported biomarker sets, both groups in our study demonstrated better and more robust classification performance in validation data sets. These novel DNA methylation biomarkers may improve lung cancer screening and ultimately contribute to improved clinical outcomes for patients. To our best knowledge, this is the first time to introduce chromatin interactions to link enhancers to their targets for biomarker study, highlighting the potential of enhancer methylation as a complement to current promoter‐based DNA methylation biomarkers. Our approach may have potential applications for other cancer types and could be a valuable direction for future research in the field of cancer biomarker discovery.